PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Pada PT. NISAN ABADI JAYA) - Rina Loliyana; Misran Hadi; Evi Meidasari (Jurnal Manajemen dan Bisnis (JMB), 2023)
ABSTRACT This study aims to determine the effect of training on employee work productivity with motivation as a mediating  variable. This study took a sample of 54 with a population of 115. The data collection technique was to  distribute questionnaires to respondents. The analysis method itself uses Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Linearity Test, Simple Regression Test, t Statistics Test, f Statistical Test, R2 Determinant Coefficient Test, and Path Analysis. The results of this study indicate that the training variable has a significant effect on the motivation variable because it has a t value of 5.177 t table 1.675, the training variable has a significant influence on the work productivity variable because it has a t value of 4.249 t table 1.675, the motivation variable has a significant influence. significant to the work productivity variable because it has a t value of 5.920 t table  1.675,  and  the  training  variable  does  not  have  a  significant  indirect  effect  on  the  work productivity variable through motivation as an intervening variable, which is  0.299. Based on the decision making, the result of the indirect effect is 0.583 x 0.513 = 0.299. Based on decision making, the result of the indirect effect is 0.299 from the direct effect of 0.583. So, Ha is rejected and Ho is accepted. Keywords: Training, Work Productivity, Motivation